Computation of a function of a matrix with close eigenvalues by means of the Newton interpolating polynomial - Kurbatov, V.G.; Kurbatova, I.V. (Linear & multilinear algebra, 2016)
An algorithm for computing an analytic function of a matrix is described. The algorithm is intended for the case where has some close eigenvalues, and clusters (subsets) of close eigenvalues are separated from each other. This algorithm is a modification of some well known and widely used algorithms. A novel feature is an approximate calculation of divided differences for the Newton interpolating polynomial in a special way. This modification does not require to reorder the Schur triangular form and to solve Sylvester equations.